Learning From the Patient's Perspective: A View From a Patient With Sickle Cell Disease - Monica Lypson; Andrew Campbell; Paula Ross; Arno Kumagai; Heather Davis (Association of American Medical Colleges, 2010)
Abstract This resource represents how using multimedia artifacts in education is an engaging way to involve patients and health professionals in discussions of chronic disease, specifically sickle cell anemia and its potential impact on patients. These artifacts can be ideal for helping others understand perspectives on illness shared between and among patients as they seek role models and information on self-management of their condition. The goals of this case presentation are for learners to understand the multiple sides of patient care and how previous experiences influence patients' perceptions and behavior with their care. The use of multimedia, in this case, photographs and videos, can stimulate health care providers to consider the influence illness has on the everyday lives of their patients. Students have found these clips to be useful in stimulating their thinking about the patient's perspective. They also helped them understand the many faces of pain experiences. Finally, patients and adolescents in particular with sickle cell find the images powerful, allowing them a path forward as they enter adulthood, demonstrate role models and provide suggestions/insights on how to deal with sickle cell, chronic disease, and health professionals.